Effect of Commitment, Compensation, and Leadership on Employee Performance and Sharia Engagement as Variable Intervening - Indira Basalamah; Mansyur Ramli; H. Bahar Sinring; Roslina Alam (AIBPM Publisher, 2018)
Sharia engagement is an individual, physical, emotional and spiritual attachment that is influenced by belief, justice, balance, freedom and responsibility towards the organization. The object of research is the employees of sharia banking located in Makassar City. Through cluster techniques sampling of samples processed in the study were 185 employees spread across 13 sharia banking offices. Keywords: Commitment, Compensation, Leadership, Sharia Engagement, and Employee Performance